Critical Discussion Analysis of Online News Media Text in Implementation of PSBB during Pandemic Covid-19 - Pratiwi, Retna Isti; Setiawan, Teguh (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Online media plays an important role in reporting during the pandemic. Various case issues and changes in people's behavior are easily accessible through online news. This study aims to explain how the structure of the text which includes the macro structure, micro structure and superstructure is displayed in the news text about the implementation of PSBB at the closing ceremony of McDonald's, cognitive analysis and social analysis that influence journalists as news writers in revealing PSBB violations. The research method used is a qualitative method with the technique of critical discourse analysis of the Teun A. Van Dijk model which includes 3 dimensions, namely the dimensions of text, social cognition and social context. The data is in the form of online news published in three media, namely kompas.com, tempo.com and detik.com which aired in May 2020 with the news theme "Closing McDonald's at Sarinah Jakarta Outlets". The results of the study show that there has been a violation of the PSBB implementation during the Covid1-9 pandemic. Violations committed in the form of not wearing masks, not maintaining social distance Utilization of social cognition and access to influence the minds of readers through discourse are used by news sources and journalists to build public awareness in supporting the implementation of PSBB. This can be seen in persuasive sentences and appeals not keeping a distance The use of social cognition and access to influence the minds of readers through discourse is used by news sources and journalists to build public awareness in supporting the implementation of PSBB. This can be seen in persuasive sentences and appeals not keeping a distance. The use of social cognition and access to influence the minds of readers through discourse is used by news sources and journalists to build public awareness in supporting the implementation of PSBB. This can be seen in persuasive sentences and appeals.